Factors of construction injuries at Perak, Pulau Pinang and Kedah construction site / Mohd Norazman Abdul Kholid - Abdul Kholid, Mohd Norazman (2021)
The construction sector is a one sector which is the sector most vulnerable to accidents. However, as one developing country, Malaysia is also not lacking in the construction industry. The country is booming, expanding world of construction. However, the extent to which the security level adopted can reduce the accident thus construction site is free accidents and injuries to construction workers. Statistic issued by DOSH and NIOSH also describes the construction sector be at a critical stage and need for change and reassessment by the responsible party. In a study conducted at several construction sites are some of the causes and types of accidents that often happen on construction sites. This study was also conducted on all construction sites to be used as a study by distributing sets of questionnaires. Data were analysed using SPSS Version 21. Results from the analysis showed some differences about the nature of the accident, the cause of accidents and the level of awareness among construction workers depend on a case study. From the study also, many respondents agreed that if a nurse or site safety is placed at construction sites to control the behaviour of construction workers on a construction site.